SAE Technical Paper Series 2014
DOI: 10.4271/2014-01-2708
|View full text |Cite
|
Sign up to set email alerts
|

CFD Investigation on the Influence of In-Cylinder Mixture Distribution from Multiple Pilot Injections on Cold Idle Behaviour of a Light Duty Diesel Engine

Abstract: Cold idle operation of a modern design light duty diesel engine and the effect of multiple pilot injections on stability were investigated. The investigation was initially carried out experimentally at 1000rpm and at −20°C. Benefits of mixture preparation were initially explored by a heat release analysis. Kiva 3v was then used to model the effect of multiple pilots on in-cylinder mixture distribution. A 60° sector of mesh was used taking advantage of rotational symmetry. The combustion system and injector arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our analysis revealed that the spark assistance with appropriate injector spray pattern and fuel injection strategy enhanced GCI combustion at cold idle conditions. The effectiveness of spark-assisted cold starting strategy has been also reported by other researchers [32][33][34][35].…”
supporting
confidence: 71%
“…Our analysis revealed that the spark assistance with appropriate injector spray pattern and fuel injection strategy enhanced GCI combustion at cold idle conditions. The effectiveness of spark-assisted cold starting strategy has been also reported by other researchers [32][33][34][35].…”
supporting
confidence: 71%
“…Generally, when a spark plug was used, an early ignition occurred near the spark plug, and the combustion efficiency of the case with spark plug assistance was found to increase by 11% compared to the case without it. Other studies [40][41][42] have also demonstrated the effectiveness of spark assistance in enhancing engine combustion performance under cold-starting conditions.…”
Section: Overview Of Previous Pre-doe Spark Assistance Studiesmentioning
confidence: 99%
“…Nevertheless, they still cover a quite wide range of engine operation, including typical pilot and main injection events, and are also representative of novel injection strategies targeted at partially premixed charge compression ignition operation with quite advanced injection timings. For example, typical pilot injections start well in advance of the main injection, about 20-40° crank angle before top dead centre [82][83][84], or even 90° crank angle before top dead centre for highly premixed charge operation, e.g. [85], hence in-cylinder pressures in such cases can be significantly lower than the main injection event.…”
Section: Boundary Conditions and Test Casesmentioning
confidence: 99%